Potential of Local Plants from Buton Island as a Source of Learning Biology - Agus Slamet; S. Hafidhawati Andarias; Dyah Pramesthy Isyana Ardiyati; Yenni B.; W.D. Fatma Inang (Bioedusiana: Jurnal Pendidikan Biologi, 2020)
The aims of this study is to identify the diversity of local plants on the island of Buton, the results of the identification of potential learning resources, the potential of local plants on the island of Buton to be used as a source of learning to achieve basic skill in the 2013 curicullum. This researches is a method of exploratory research that contains  survey, observation and interview for the use of local plants. The data analysis used is the exploratif analysis and analysis of potential learning resources through a literature review. The results of this study indicate that 23 species of local plants have been identified on Buton Island to be used as a functional food, coloring agents, plastic subtitutes, herbs and spices, medicines and cosmetics, and raw materials for crafts/textiles. The local plants are Amorpophalus sp., Dioscorea alata, Setaria italica, Maranta arundinaceae, Cajanus sp., Oryza sativa, Indigofera sp., Tectona grandis, Hibiscus tiliaceus, Ficus septica, Pisonia alba, Musa balbisinia, Sterculia sp., Amomum sp., Spondias pinnata, Sandoricum koetjape, Averhoa balumbi, Eleutherine palmifolia, Donax canniformis, Pandanus sp., Lygodium circinatum, Bambusa blumeana, and lapi. Based on the requirements of fulfilling local potential as a source of learning that includes aspects of potential clarity, conformity to goals, clarity of objectives, clarity of information revealed, clarity of exploration guidelines and clarity of expected outcomes. the results of research in the form of local plant potential on Buton Island to achieve K.D-3.2 2013 curriculum on Indonesian Biodiversity Materials can be used as a source of biology learning for SMA class X.